Three-Way Interaction Model for Turnover Intention of Construction Professionals: Some Evidence from Turkey - UĞURAL, MEHMET NURETTİN; Giritli, Heyecan (ASCE-AMER Soc. Civil Engineers, 2021)
Voluntary turnover of key employees with scarce skills and tacit knowledge has a potential influence on the competitive advantage of construction organizations. Although much research has been conducted to find out causes of turnover intention, there is limited research in the construction context, particularly considering the influence of the psychological perspective. In this study, using data from 351 construction professionals in the Turkish construction industry and utilizing a three-way moderated moderation model, we examined the interaction effects of psychological factors, operationalized in terms of organizational identification and perceived external prestige, on turnover intention within the boundary of gender differences. Analysis of the responses demonstrates that considering organizational identification, perceived organizational prestige, and gender independently may lead to the underprediction of the turnover intention of employees in construction organizations. The results indicate that organizational identification and perceived organizational prestige have an impact on construction professionals' turnover intention in a condition boundary for gender differences. On this basis, this study may provide important insights for human resource practitioners in identifying potential employees that are likely to have lower turnover intention. It is also of relevance to managers in retaining valued professionals in construction firms.
Keywords: Turnover Intention; Construction Employees; Moderated Moderating Effect; Identification; Prestige; Gender